Antiemetics: ASCO guideline update - Hesketh, Paul; Kris, Mark G.; Basch, Ethan; Bohlke, Kari; Barbour, Sally Y.; Clark-Snow, Rebecca Anne; Danso, Michael A.; Dennis, Kristopher; Dupuis, L. Lee; Dusetzina, Stacie B.; Eng, Cathy; Feyer, Petra C.; et al. (Journal of clinical oncology, 2020)
Purpose: To update the guideline to include new anticancer agents, antiemetics, and antiemetic regimens and to provide recommendations on the use of dexamethasone as a prophylactic antiemetic in patients receiving checkpoint inhibitors (CPIs). Methods: ASCO convened an Expert Panel and updated the systematic review to include randomized controlled trials (RCTs) and meta-analyses of RCTs published between June 1, 2016, and January 24, 2020. To address the dexamethasone and CPI question, we conducted a systematic review of RCTs that evaluated the addition of a CPI to chemotherapy. Results: The systematic reviews included 3 publications from the updated search and 10 publications on CPIs. Two phase III trials in adult patients with non-small-cell lung cancers evaluating a platinum-based doublet with or without the programmed death 1 (PD-1) inhibitor pembrolizumab recommended that all patients receive dexamethasone as a component of the prophylactic antiemetic regimen. In both studies, superior outcomes were noted in the PD-1 inhibitor-containing arms. Other important findings address olanzapine in adults and fosaprepitant in pediatric patients. Recommendations: Recommendations for adults are unchanged with the exception of the option of adding olanzapine in the setting of hematopoietic stem cell transplantation. Dosing information now includes the option of a 5-mg dose of olanzapine in adults and intravenous formulations of aprepitant and netupitant-palonosetron. The option of fosaprepitant is added to pediatric recommendations. There is no clinical evidence to warrant omission of dexamethasone from guideline-compliant prophylactic antiemetic regimens when CPIs are administered to adults in combination with chemotherapy. CPIs administered alone or in combination with another CPI do not require the routine use of a prophylactic antiemetic. Additional information is available at www.asco.org/supportive-care-guidelines.
Gesehen am 29.10.2020